Scanning Tunneling Microscopy/Spectroscopy on Perovskite Oxide Thin Films Deposited In Situ. Issue 5 (16th September 2014) - Hitosugi, Taro; Shimizu, Ryota; Ohsawa, Takeo; Iwaya, Katsuya
Abstract Complex oxide surfaces and interfaces, consisting of two or more cations and oxygen anions, have attracted a great deal of attention because their properties are crucial factors in the performance of catalysts, fuel cells, and Li‐ion batteries. However, atomic‐scale investigations of these oxide surfaces have been hindered because of the difficulties in surface preparation. Here, we demonstrate atomic‐scale surface studies of complex perovskite oxides and the initial growth processes in oxide epitaxial films deposited on (✓13 × ✓13)‐R33.7° reconstructed SrTiO3(001) substrates using a scanning tunneling microscope integrated with a pulsed laser deposition system. The atomically ordered, reconstructed SrTiO3(001) surface is stable under the typical conditions necessary for the growth of oxide thin films, and hence is considered suitable for the study of the initial growth processes in oxide films. The atomic‐scale microscopic/spectroscopic characterizations performed here shed light on the microscopic origin of electronic properties observed in complex oxides and their heterostructures.